Evaluation of a Tap-Based Smartphone App for Heart Rate Assessment During Asphyxia in a Porcine Model of Neonatal Resuscitation - Johnson, Peter A.; Morina, Nicolò; O'Reilly, Megan; Lee, Tze-Fun; Cheung, Po-Yin; Schmölzer, Georg M. (Frontiers in Pediatrics, 2019)
Objectives: Heart rate (HR) is the most significant parameter to assess a newborn’s clinical status at birth. Recently, novel technologies including smartphone applications have been suggested for HR assessment during neonatal resuscitation. The aim of this study was to evaluate the accuracy, speed, and precision of the NeoTapLifeSupport (NeoTapLS) smartphone application using a digital stethoscope (DS) for HR assessment during neonatal resuscitation. Design: Newborn piglets (n=20, 1-3 days, 1.7-2.4kg) were anaesthetised, intubated, mechanically ventilated, and subjected to 30 min of hypoxia, followed by asphyxia. Asphyxia was induced by clamping the endotracheal tube and disconnecting the ventilator, until asystole was confirmed by zero carotid blood flow (CBF). Setting: Experimental setting. Subjects: Asphyxia-induced newborn piglets. Interventions: During asphyxia, HR assessments were performed with a DS using the NeoTapLS smartphone application, and compared to 6-sec method (6sec), and 10-sec method (10sec). Measurements and Main Results: Accuracy of obtained HRs was compared to CBF and electrocardiogram and assessment time using NeoTapLS, 6sec, and 10sec were also measured. The mean(SD) HR with the NeoTapLS was 68(26), compared to CBF with 68(27) bpm, 6sec with 68(27), and 10sec with 66(26) bpm during asphyxia. Bland-Altman analysis revealed no difference between HR using the NeoTapLS, 6sec, 10sec, compared to CBF HR, with NeoTapLS showing the smallest difference between 95% limits of agreement. The median (IQR) time required to obtain a HR using the NeoTapLS was 3(2-4)sec, compared to 6(6-7) and 10(10-11) sec for 6sec and 10sec, respectively. Conclusions Our data suggests that the NeoTapLS is accurate, fast, and precise during neonatal asphyxia to assess heart rate.